Electrically detected spin resonance - Błoniarz, Jacek; Wilamowski, Zbysław (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
An amplitude and a line shape of electrically detected signal of spin resonance are discussed. Since the signal scales with changes of spin polarization under resonance condition it is proportional to longitudinal spin relaxation. The analysis shows that such a method of detection of spin resonance is especially useful for low dimensional semiconductor structures.
Optica Applicata, Vol. 36, 2006, nr 2-3, s. 285-289
Keywords: optyka; spin resonance; spin-orbit coupling; spin relaxation